Congenital antithrombin deficiency in patients with splanchnic vein thrombosis. (16th January 2020) - Baiges, Anna; de la Morena‐Barrio, María Eugenia; Turon, Fanny; Miñano, Antonia; Alberto Ferrusquía, Jose; Magaz, Marta; Reverter, Juan Carlos; Vicente, Vicente; Hernández‐Gea, Virginia; Corral, Javier; García‐Pagán, Juan Carlos
Abstract: Background and aims: Splanchnic vein thromboses (SVT) are a rare condition that can be life‐threatening. The most severe thrombophilia associated to SVT is antithrombin (AT) deficiency, usually caused by SERPINC1 mutations. Although transitory AT deficiencies and congenital disorders of the N‐glycosylation pathways (CDG) have been recently reported as causes of AT deficiency, the current AT clinical screening still only includes anti‐FXa activity. This study aims to (a) improve the detection of AT deficiency in SVT and (b) characterize the features of AT deficiency associated with SVT. Methods: The study was performed in 2 cohorts: (a) 89 SVT patients with different underlying etiologies but in whom AT deficiency had been ruled out by classical diagnostic methods; and (b) 271 unrelated patients with confirmed AT deficiency and venous thrombosis. AT was evaluated by functional (anti‐FXa and anti‐FIIa) and immunological methods (ELISA, crossed immunoelectrophoresis, western blot), and SERPINC1 sequencing was performed. Results: In 4/89 patients (4.5%) additional alterations in AT were found (two had SERPINC1 mutations, one had a specific variant causing transient AT deficiency and one patient had CDG). In 11 of the 271 patients (4.1%) with AT deficiency and thrombosis, thrombosis was located at the splanchnic venous territory. Conclusions: Antithrombin deficiency may be underdiagnosed by current clinical screening techniques. Therefore, a comprehensive AT evaluation should be considered in cases of rethrombosis or doubtful interpretation of anti‐FXa activity levels. SVT is a relatively common localization of the thrombotic event in patients with congenital AT deficiency.